Influence Of Video Games on Expressive Skills For English Learners Among College Students - Alviansyah Nugraha; Yeni Rahmawati (Journal of English Language Learning, 2025)
This study investigates the influence of playing video games on the development of English language skills, with a particular focus on expressive abilities among college students. The research explores how video games, as interactive and immersive environments, enhance learners’ confidence, motivation, and communication skills in English. Using a quantitative approach, data were gathered through questionnaires distributed to respondents with varying gaming habits and language proficiency levels. The findings reveal that video games positively influence language acquisition. A significant portion of respondents reported improvements in articulating thoughts clearly, understanding idiomatic expressions, and engaging in real-life English conversations. Over 80% agreed that video games make learning English more enjoyable and interactive, while 54% acknowledged increased confidence in using English after playing. Moreover, multiplayer games provided opportunities for real-time communication and quick linguistic responsiveness, further developing expressive and social language skills. Video games could be a powerful language learning tool by addressing societal misconceptions and technical challenges. The research concludes that video games are not only a source of entertainment but also a valuable medium for fostering English language proficiency, particularly in expressive communication. This underscores the need for further exploration of gamified learning to unlock its full educational potential.